Para-fuzzy logic controller - Abe, J. M.; Negoita, M. G.; Howlett, R. J.; Jain, L. C. (Springer, 2004)
In this paper we present a logic controller based on ideas of Fuzzy logic and Paraconsistent Annotated Logic. The combination of both logics brings a new approach to fuzzy, inconsistent and paracomplete concepts. The simulations using the Aim-Spice 1.5.a software and the masks of integrated circuit of a paraconsistent system built in technical fall-custom for a ES2-CMOS 1.2 mum digital process are also presented. This IC is compatible with the TTI family and it can be connected to Fuzzy controllers to compose the Para-Fuzzy Logic Controller. Such controller can be applied to expert systems and autonomous mobile robot's control according to an example presented in this work.
Keywords: fuzzy logic; paraconsistent annotated logic; logic controller; control systems